Navigating the Binary: A Qualitative Study on the Lived Experiences and Coping Mechanisms of Gender-Diverse College Students - Anthony M. Mon; Emelyn M. Bugayong; The PRMSU BEEd Third-Year Research Group (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This study explores the systemic intersection between institutional regulations and the daily sociallives of gender-diverse students (N=26) within a regional university campus. Using qualitativeanalysis across four core Statements of the Problem (SOPs), the findings reveal a campusenvironment characterized by conditional inclusivity. While structural metrics show high peeracceptance and active diversity programming, participants note persistent challenges, includinggenerational microaggressions from faculty and the structural erasure of bisexual and asexualidentities.Systemic friction centers primarily on binary infrastructure and rigid uniform regulations, whichinduce severe bathroom navigation anxiety and place an unnecessary administrative burden onstudents seeking dress code exemptions. To manage these daily minority stressors, students utilizecalibrated classroom advocacy alongside self-protective strategic silence. Students also relyheavily on relational buffers—such as secure queer peer networks—and intentional intrapersonalisolation, frequently retreating to quiet campus spaces like the library to maintain psychologicalwell-being.The study highlights a critical gap between top-down administrative policies and the lived realitiesof students. To address these issues, this paper offers actionable institutional recommendations,including retrofitting all-gender spatial facilities, decoupling uniform guidelines from genderbinaries, and codifying protective local anti-discrimination ordinances.